Kupu-kupu dengan Laser Cut sebagai Sumber Ide Penciptaan Busana Pesta - Jinan, Nisa El; Wahyuningsih, Urip (BAJU: Journal of Fashion and Textile Design Unesa, 2023)
Butterfly has a unique beauty, this unique beauty makes those who see it interested. The purpose of this research is to describe the process of making and finished dresses with the source of the idea, namely butterflies, using the laser cut technique. This research method uses a three stages design process approach or three stages of the design process. This method consists of 3 stages of research: problem definition and research, creative exploration and implementation. In the early stages of determining the design direction, namely making women's dresses with butterfly inspiration made for young women with the art of beat type. In the second stage, the researcher made a moodboard and developed 10 sketch designs for dresses in the form of one piece dresses. The two selected designs were created using construction and draping patterns. The implementation stage is by applying laser cut butterflies and ruffles as the center of interest in the party dress. The process of making a laser cut starts from preparing the leather jahard fabric that has been laser cut in the shape of a butterfly, then it is pinned according to the design. The result of the party dress is as expected, namely a dress that can fit the body properly for an art of beat type woman and applies laser cut decoration and ruffles certain parts that apply the center of interest design principle.